Non-islet-cell tumor hypoglycemia secondary to malignant phyllodes tumor of the breast - Lee, Si Min (2024)
Background/Objective: Non–islet cell tumor hypoglycemia (NICTH) is an uncommon condition, of which only a few cases caused by malignant phyllodes tumor of the breast have been reported. We describe a case of NICTH secondary to malignant phyllodes tumor with good response to glucocorticoid therapy. Case Report: A 62-year-old woman with a rapidly enlarging left breast mass presented with drowsiness and a capillary blood glucose level of 32.4 mg/dL. Her plasma glucose and insulin levels were 36.0 mg/dL (reference range, 72-144 mg/dL) and 0.6 mIU/L (reference range, 0.0-25.0 mIU/L), respectively. Her beta-hydroxybutyrate and c-peptide levels were undetectable. The insulin-like growth factor (IGF)-I and IGF-II levels were 37 μg/L (reference range, 43-220 μg/L) and 1062 ng/mL (reference range, 333-967 ng/mL), respectively, with an IGF-II:IGF-I molar ratio of 29.4. Prednisolone 30 mg per day was initiated with improvement in hypoglycemia. Outpatient flash glucose monitoring profile was stable with mild hypoglycemia (glucose level, 54-68.5 mg/dL) detected 5% of the time. The patient underwent left mastectomy with axillary clearance 4 weeks later. Histology was reported as malignant phyllodes tumor with extensive ductal carcinoma in situ. Prednisolone was stopped after surgery. The patient was treated with letrozole and adjuvant radiotherapy. There was no recurrence of hypoglycemia during the subsequent 24-month follow-up. Discussion: The mainstay of treatment for NICTH is surgical resection of the culprit tumor. Although glucocorticoid treatment has also been widely used for NICTH, few reports have demonstrated efficacy for NICTH secondary to phyllodes tumor. Conclusion: We report a rare case of malignant phyllodes tumor of the breast resulting in NICTH and demonstrated good response to glucocorticoids as a bridge to definitive surgery.